The effect of a police sectoral communication network on crime rates in Bogotá, Colombia (2017)
In an evaluation of the police sectoral communication network in Bogotá, Colombia, we show that the police response to criminal activity is enhanced with better nodal communication in the sectoral network. Restricted and unrestricted networks are considered to reduce crime and improve policing coverage in adjacent areas. We find that nodal communication reduces the most frequent crimes and raises the efficiency of police units. The results indicate that crime is reduced for localities adjacent to each other with lower unemployment, a higher level of education, and with more communication in the sectoral network.